Maternal activity, anxiety, and protectiveness during moderate nutrient restriction in captive baboons (Papio sp.). Issue 4 (11th May 2018) - Light, Lydia E. O.; Bartlett, Thad Q.; Poyas, Annica; Nijland, Mark J.; Huber, Hillary F.; Li, Cun; Keenan, Kate; Nathanielsz, Peter W.
Abstract: Background: We hypothesized that maternal nutrient restriction (NR) would increase activity and behavioral indicators of anxiety (self‐directed behaviors, SDBs) in captive baboons ( Papio sp.) and result in more protective maternal styles. Methods: Our study included 19 adult female baboons. Seven females ate ad libitum (control group), and eight females ate 30% less (NR group) and were observed through pregnancy and lactation. Results: Control females engage in higher rates of SDB than NR females overall ( P ≤ .018) and during the prenatal period ( P ≤ .001) and engage in more aggressive behavior ( P ≤ .033). Control females retrieved infants more than NR females during weeks 5‐8 postpartum ( P ≤ .019). Conclusions: Lower SDB rates among prenatal NR females reduce energy expenditure and increase available resources for fetal development when nutritionally restricted. Higher infant retrieval rates by controls may indicate more infant independence rather than maternal style differences.